МОДЕЛЮВАННЯ ВІДБИВНОЇ ПЛАВИЛЬНОЇ ПЕЧІ, ОСНАЩЕНОЇ ВИХРОВОЮ КАМЕРОЮ З ДУГОВИМ ІНДУКТОРОМ - Гориславець, Ю.М.; Пеньковий, Т.О. (Інститут електродинаміки Національної академії наук України, 2023)
A scheme of a reverberatory furnace for melting aluminium waste in a vortex flow of melt created by a curve inductor in a separate cylindrical chamber is presented. The vortex chamber, which is connected to the furnace's melting bath by means of two channels, performs two functions in this furnace: it stirs the molten metal in the bath and creates a vortex funnel into which the pulverized charge is fed. A mathematical model for numerical research of electromagnetic and hydrodynamic processes in such a system is formulated. The influence of the angle of attachment of the suction and pumping channels to the side cylindrical surface of the vortex chamber on its parameters was determined. Such parameters were the average speed of liquid metal in the furnace bath, the melt flow through the cross sections of the connecting channels and the average angular speed of the metal in the chamber. It was established that the angle of the connection of the suction channel has little effect on the operation of the chamber, in contrast to the angle of the pumping channel, which in order to achieve maximum stirring of the metal in the bath should take minimum values, and to create a maximum funnel should be more than 500. Considerations are given regarding the compromise values of this angle, which can ensure the necessary operation of the chamber, both from the point of view of the liquid metal stirrer in the furnace bath, and from the point of view of the rotating device of the metal in the chamber. References 8, figures 5.